KARAKTERISASI MODUL CYCLICALLY PURE (CP)-INJEKTIF - Nia Yulianti; Hanni Garminia Y (Journal of Fundamental Mathematics and Applications (JFMA), 2020)
This research deals with the structure of cyclically pure injective modules over a commutative ring R. If I be an ideal of R, proved that any CP-injective R/Imodul is also CP-injective as an R-module. The main result of research is the existance of CP-injective R-module if there is an R-module. More over, we deal characterization of CP-injective module which is related to proper essential ctclically pure extension. It is shown that R-modul D is cyclically pure injective if and only if D has no proper essential cyclically pure extension.